P. 1
Set Theory Lecture Notes

# Set Theory Lecture Notes

|Views: 1,958|Likes:

Published by: yusuf on Jan 17, 2010

### Availability:

Read on Scribd mobile: iPhone, iPad and Android.
See more
See less

11/22/2012

pdf

text

original

In this subsection, we show that if (N1,S1,O1) is a structure satisfying the
Peano’s Axioms (deﬁned below), then there is a (unique) bijection f :N−→N1
such that f(S(x)) = S(f(x)) and f(0) = 01 for all x∈N. This will show that a
structure satisfying Peano’s Axioms is unique “up to isomorphism”. We make
this more precise:

Let N be a set, S : N −→ N a function and 0 ∈ N an element. Suppose
that the triple (N ,S ,0 ) satisﬁes the following:

PA1. S is a one to one function from N into N .

PA2. If X is a subset of N with the property that

a) 0 ∈X,

b) For all x∈X, S (x)∈X,

then X =N .

Then we say that the triple (N ,S ,0 ) satisﬁes the Peano axioms. Of course,
for a triple that satisﬁes the Peano axioms, all the results of the previous sections
xxx hold.

Theorem 11.11.1 Any two triples (N ,S ,0 ) and (N ,S ,0 ) satisfying the
Peano Axioms are “isomorphic”, i.e. there is a bijection f : N −→ N such
that f(0 ) = 0 and f(S (x)) = S (f(x)) for all x∈N .

Proof: Since the composition and the inverse of isomorphisms is clearly an
isomorphism, we may suppose that (N ,S ,0 ) = (N,S,0). Deﬁne f :N−→N
by the rule,

f(0) = 0

and

f(S(x)) = S (f(x)).

By Theorem 11.8.1 f is a function. We just need to prove that it is one to one
and that it is unique.

We ﬁrst show that f is one to one. Assume f(x) = f(y). We will show that
x = y. We proceed by induction on x.
Assume x = 0. Then f(y) = 0 . If y = 0, then y = S(x1) and so 0 = f(y) =
f(S(x1)) = S (f(x1)), contradicting the fact that 0 is not in the range of S .
Thus y = 0 = x.

Assume now x = 0. Then x = S(x1). So S (f(x1)) = f(S(x1)) = f(x) =
f(y). In particular f(x) and f(y) are nonzero. Therefore y = 0 as well. Let

y = S(y1). Then S (f(x1)) = f(y) = f(S(y1)) = S (f(y1)). Since S is one to
one, it follows that f(x1) = f(y1). By the inductive hypothesis x1 = y1. Hence
x = S(x1) = S(y1) = y. This proves that f is one to one.
We now show that if f is another such function then f = f . By assump-
tion f(0) = 0 = f (0). Assume f(x) = f (x). Then f(S(x)) = S (f(x)) =
S (f (x)) = f (S(x)). This proves that f = f .

Chapter 12

Integers

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->